MACROECONOMIC VOLATILITY, SECURITY ALLOCATIONS, AND MATERNAL MORTALITY IN NIGERIA: A VECTOR ERROR CORRECTION APPROACH - Sophia Maimuna John (Research Parks Publishers, 2026)
The intersection of fiscal reallocations driven by internal security threats and open-economy monetary shocks presents a profound policy challenge for resource-dependent developing nations. While traditional public health literature focuses heavily on clinical or micro-level institutional determinants of maternal death, it frequently overlooks the macro-fiscal and monetary transmission channels that dictate real health-resource efficacy. This study empirically investigates the extent to which exchange rate depreciation mediates or exacerbates the relationship between military expenditure and maternal mortality in Nigeria. Utilizing annual time-series data spanning from 2000 to 2024, the study employs a rigorous Vector Error Correction Model (VECM) under the Johansen cointegration framework to separate long-run structural equilibria from short-run dynamic innovations among uniformly integrated I (1) series. The long-run normalized structural equation reveals a stark dual-threat mechanism affecting maternal health. First, military expenditure exhibits a statistically significant positive elasticity (β= 0.245), validating the Samuelsonian